2014
DOI: 10.1371/journal.pone.0104180
|View full text |Cite
|
Sign up to set email alerts
|

Selective Control of Attention Supports the Positivity Effect in Aging

Abstract: There is emerging evidence for a positivity effect in healthy aging, which describes an age-specific increased focus on positive compared to negative information. Life-span researchers have attributed this effect to the selective allocation of cognitive resources in the service of prioritized emotional goals. We explored the basic principles of this assumption by assessing selective attention and memory for visual stimuli, differing in emotional content and self-relevance, in young and old participants. To spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 72 publications
1
35
2
3
Order By: Relevance
“…Behavioral studies provide further support for the notion that older adults engage prefrontal resources in order to help increase positivity and/or diminish negativity of attention and memory by showing that higher executive function is associated with higher positivity among older adults but not younger adults (Isaacowitz et al, 2009b, Knight et al, 2007, Mather and Knight, 2005, Petrican et al, 2008, Sasse et al, 2014, Simón et al, 2013, but see Foster et al, 2013). …”
Section: Relations Between Emotional Processing In Aging and Brain Fumentioning
confidence: 74%
“…Behavioral studies provide further support for the notion that older adults engage prefrontal resources in order to help increase positivity and/or diminish negativity of attention and memory by showing that higher executive function is associated with higher positivity among older adults but not younger adults (Isaacowitz et al, 2009b, Knight et al, 2007, Mather and Knight, 2005, Petrican et al, 2008, Sasse et al, 2014, Simón et al, 2013, but see Foster et al, 2013). …”
Section: Relations Between Emotional Processing In Aging and Brain Fumentioning
confidence: 74%
“…When free to look at positive, neutral, or negative pictures, a higher proportion of pictures remembered by older adults consisted of positive than negative information compared with the younger adults. Older adults also display more fixations and of longer duration for positive compared to negative or neutral pictures, a pattern different from younger adults (Sasse et al, 2014 ). A recent meta-analysis including 100 empirical studies on the positivity effect showed that the effect is robust across a wide range of tasks and stimuli (Reed et al, 2014 ).…”
Section: Discussionmentioning
confidence: 91%
“…Application and analysis was based on our previous work where older participants’ ability to control attention during highly salient distraction explained substantial variance during emotion processing (Sasse et al, 2014). …”
Section: Methodsmentioning
confidence: 99%